2022
DOI: 10.3390/ijms232112924
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Beta in Aging and Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD), is a progressive neurodegenerative disease that affects behavior, thinking, learning, and memory in elderly individuals. AD occurs in two forms, early onset familial and late-onset sporadic; genetic mutations in PS1, PS2, and APP genes cause early onset familial AD, and a combination of lifestyle, environment and genetic factors causes the late-onset sporadic form of the disease. However, accelerated disease progression is noticed in patients with familial AD. Disease-causing patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(57 citation statements)
references
References 167 publications
0
57
0
Order By: Relevance
“…The expression profile of genes associated with APP processing is downregulated in the brain of OXYS rats in the early postnatal period. Growing data on APP and Aβ suggests that they perform important physiological functions in the brain; the complete absence of the App gene in transgenic mice causes severe neurological deficits [ 40 ]. Some studies provide strong evidence that a decrease in Aβ clearance or a decrease in phagocytosis by microglia—rather than an Aβ peptide overproduction by cleavage of the APP—may be involved in AD [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression profile of genes associated with APP processing is downregulated in the brain of OXYS rats in the early postnatal period. Growing data on APP and Aβ suggests that they perform important physiological functions in the brain; the complete absence of the App gene in transgenic mice causes severe neurological deficits [ 40 ]. Some studies provide strong evidence that a decrease in Aβ clearance or a decrease in phagocytosis by microglia—rather than an Aβ peptide overproduction by cleavage of the APP—may be involved in AD [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was revealed that patients with low levels of ABCA7 develop AD neuropathology at a younger age, those with intermediate ABCA7 amounts develop it later, and the patients who developed it very late have high ABCA7 levels, just as the youngest controls, suggesting that ABCA7 acts as a blocker of AD in the early stage of this disease [ 44 ]. Lipid composition of cellular membranes can influence secretase activities and then APP processing and Aβ synthesis; therefore, it can be hypothesized that ABCA7 levels and functioning can directly modulate APP processing and subsequently Aβ production [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another recent article, Evgrafova et al have demonstrated thermoresponsive polymers varying in hydrophilicity/hydrophobicity ratio to selectively modulate Aβ aggregation kinetics [ 129 ]. Monoclonal antibodies (mAbs) directed against Aβ (bapineuzumab, crenezumab, solanezumab, and aducanumab) caused a lower incidence of AD [ 130 ]. However, increasing dosage in the later period of AD might have a negative impact on the trial results; in particular, antibodies may show off-target cross-reactivity [ 131 ].…”
Section: Influence Of Various Molecules On the Aggregation Processmentioning
confidence: 99%
“…Although good sleep plays a significant role in restoring brain functions and retaining memory, sleep is a critical factor in AD progression. The evidence of various studies has shown that sleep leads to changes in cell structure and affects the Aβ clearance mechanism [ 140 ]. Alzheimer’s patients show a significant disturbance in their circadian sleep–wake cycles, compared to similar-aged healthy individuals.…”
Section: Physical Exercisementioning
confidence: 99%